The THE ROLE OF E-BOOKS IN LEARNING PHYSICS: LITERATURE REVIEW - Lidiawati, Mutiara Putri Yaldi (Department of Physics Universitas Negeri Padang, 2024)
Currently the world is entering an era of globalization which is characterized by the utilization of the role of Information and Communication Technology (ICT) in various aspects of life. Advances in Information and Communication Technology (ICT) facilitate access to information for anyone and anywhere, this encourages changes in various aspects of life, one of which is education.Advances in technology that are increasingly developing in the world of education require teachers to be more creative in integrating this technology into learning. One of them is by utilizing electronic teaching materials, such as e-books in learning. E-book stands for